Helpful-stressful cycle? Psychological links between type of mobile phone user and stress. Issue 1 (2nd January 2016) - Lee, Yu-Kang; Chang, Chun-Tuan; Cheng, Zhao-Hong; Lin, You
Abstract : The profusion of smartphones allows more people to have access to a telephone, a computer and the Internet, all via one device. Despite this convenience, excessive usage and habitual checking can cause significant stress for smartphone users. A helpful-stressful cycle is beginning to emerge as a pattern. With this in mind, we develop a model that examines the differences between smartphone and traditional mobile phone users with regard to the relationships between four psychological factors: locus of control (LOC), social interaction anxiety (SIA), need for touch (NFT) and materialism. Our examination explores this in the context of the level of stress these two types of users experience when using their chosen phone. The results from our empirical study suggest that user type moderates the aforementioned relationships. The effects of LOC, SIA and NFT on 'technostress' are stronger for smartphone users than for traditional mobile phone users. In contrast, materialism is positively related to stress for traditional mobile phone users but not for smartphone users.